BRIX: A Gamified Application-Based Platform in German Language Learning for Beginners - Desti Nur Aini; Ibrahim Asmorodina; Erin Alida Damayanti (Future Science, 2024)
The landscape of foreign language learning has transformed due to technological advancements and innovative approaches. Among the noteworthy approaches is the integration of game elements, or gamification. Gamification has demonstrated its ability to enhance motivation, engagement, and learning outcomes across various contexts. In the realm of beginner-level German language instruction, the utilization of a gamified application-based platform presents itself as an innovative and effective method. This study is a development study that incorporates gamification elements in German language learning for beginners through an app-based platform called